Profanation of the Existential Context of Perception: Man in the “Virtual Steppes.” - Harutyunyan, Edvard (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
The culture of life organization is a context of perception that enables a person to see and comprehend the world in its entirety and to construct his own “shelter” of ontological security. Yet life itself remains an unfinished drama of searching for possibilities, during which, at certain stages, radical transformations in the cultural context of coexistence may deprive a person of those factors constitutive of his empirical nature—factors that once, more or less accurately, outlined both the present and the prospects of his life, as well as the measure and limits of his autonomy. The problem lies in the fact that each context of perception carries its own set of cultural elements, capable not only of internally undermining the social and anthropological foundations of the ontological “shelter” of a given era, but also of depriving man of his metaphysical and transcendental essence. From this perspective, the ontological order of modern individualistic (self-oriented) society appears as a form of coexistence that lacks a shared cultural context for “growing old together.” In such a society, the tendencies toward the loss of autonomous existence have emerged as challenges of anthropological magnitude, which directly erode the foundational principles of living life within a visible horizon.
Keywords: culture of life; ontological order; cultural context; autonomy; society of possibilities; virtual world; nomadic reality; existential fate; eхistential unloading